The labor market consequences of adverse financial shocks - Tito Boeri; Pietro Garibaldi; Espen R. Moen (Institute for the Study of Labor (IZA), 2012)
The recent financial crises, alongside a dramatic rise in unemployment on both sides of the Atlantic, suggest that financial shocks do translate into the labor markets. In this paper we first document that financial recessions amplify labor market volatility and Okun's elasticity over the business cycle. Second, we highlight a key mechanism linking financial shocks to job destruction, presenting and solving a simple model of labor market search and endogenous finance. While finance increases job creation and net output in normal times, it also augments their aggregate response in the aftermath of a financial shock. Third, we present evidence coherent with the idea that more leveraged sectors experience larger employment volatility during financial recessions. Theoretically, the job destruction effect of finance works as follows. Leveraged firms may find themselves in a position in which their liquidity is suddenly called back by the lender. This has direct consequences on a firm ability to run and manage existing jobs. As a result, firms may be obliged to shut down part of their operations and destroy existing jobs. We argue that with well-developed capital markets, firms will have an incentive to rely more on liquidity, and in normal times deep capital markets lead to tight labor markets. After an adverse liquidity shock, firms that rely much on liquidity are hit disproportionally hard. This may explain why the unemployment rate in the US during the Great Recession increased more than in European countries experiencing larger output losses. Empirically, the paper uses a variety of datasets to test the implications of the model. At first we identify crises that, just like in the model, caused a sudden reduction of liquidity to firms. Next we draw on sector-level data on employment and leverage in a number of OECD countries at quarterly frequencies to assess whether highly leveraged equilibria originate more employment adjustment under financial recessions. We find that highly leveraged sectors and periods are associated with higher employment- to-output elasticities during banking crises and this effect explains the observation of higher Okun's elasticities during financial recessions. We also argue that the effect of leverage on employment adjustment can be interpreted as a causal effect, if our identification assumptions are considered plausible. All this amounts essentially for a test of the labor demand channel of adjustment.
Keywords: G1; J2; J6; 330; financial shocks; matching; Okun's elasticities